Preparation of bio-eco based cellulose nanomaterials from used disposal paper cups through citric acid hydrolysis. (1st May 2020) - Nagarajan, K.J.; Balaji, A.N.; Kasi Rajan, S. Thanga; Ramanujam, N.R.
Highlights: CNCs & CNFs are extracted from Used Disposal Paper Cups by citric acid hydrolysis. TGA analysis shows that CNCs (76 wt.%) and CNFs are thermally stable until 308 °C and 305 °C. TEM shows that CNCs (76 wt.%) appears rod-like structure with the range of 13.7 ± 0.6 nm width. Characterized CNCs(76 wt.%) has the potentiality to replace the artificial nano particles. Abstract: The Used Disposal Paper Cups (UDPCs) have become a concern to the solid waste management sector as scientists triggered the problems in recent years, to proceed forward in developing the process for this issue. Based on this concern, the present study emphasizes on the isolation of a novel bio-eco based Cellulose NanoCrystals (CNCs) from UDPCs through citric acid hydrolysis. The effect of acid concentration on microstructure and yield of CNCs are highlighted. The optimized yield (55 wt.%) has an appearance of rod-like structure with a width of 13.7 ± 0.6 nm which results due to 76 wt.% of acid hydrolyzed CNCs. The colloidal stability, crystallinity index, presence of functional groups and elemental composition in CNCs (76 wt.%) were identified by employing zeta potential, XRD, conductometric test and FTIR techniques. Finally, the thermal stability of CNCs (76 wt.%) was investigated by thermo-gravimetric analysis.